Project Based Learning Implementation to Improve Students' Problem Solving Ability and Honesty - Rahman, Erik; Mashuri, Mashuri; Hendikawati, Putriaji (Unnes Journal of Mathematics Education, 2017)
The purpose of this research is to know the learning completeness, problem solving ability improvement, and honesty improvement by using Project Based Learning. This research used quantitative method.The data were taken by using documentation, observation, and test. The result of the research were 1) the completeness percentage of problem solving ability of experimental class is more than 75%; 2) the problem solving ability of experimental class improved after using Project Based Learning method which was shown by: the higher average of posttest rather than the pretest, gain index showed the improvement of problem solving ability in moderate category, that was 0,66, and the average score ofproblem solving ability of experimental class was higher than the control class; 3) the improvement of students’ honesty character proved by: the higher average of postest of honesty character rather than the pretest, gain index showed improvement in honesty character that is 0,25 (low category), the average of honest character improvement of experimental is higher than the control class.